Leading the Way or Not: Racial Diversity of Leadership in Community Development Organizations. - Bolduc, Michele.; Kurtz, Corey.; Meredith-Warren, Rachel.; Resende, Flavia. (Tufts University. Tisch Library., 2018)
2007 M.A. in Urban and Environmental Policy and Planning Field Project. Client: The Alliance - Advancing Community Development by Confronting Racism.